Digital Technologies and Alternative Justice Models: Moving Away from Carceral Politics (abstract accepted) - Dell'Orso, A. (Popular Culture and World Politics v16 conference: Political Violence and Popular Culture, 2025)
Systemic and institutional oppression, hierarchies, violence, and marginalization are reproduced and exacerbated in digital spaces (Çelik, 2023; Kuhn et al., 2023; Loh, 2022). The intersection of policing and carcerality, surveillance capitalism (Zuboff, 2015), censorship, and isolation raises important questions about accountability, justice, and social change. With the omnipresence of social media, CCTVs, and cell phones, ubiquitous surveillance has become normalized, particularly in settler colonies such as the United States (U.S.). This constant monitoring has strong implications for privacy and autonomy, including the use of digital shaming as a form of punishment because the U.S. carceral culture thrives on individualistic and punitive features like shame, fear, disconnection, and control. Indeed, there is potential for shame to be applied constructively for social change efforts, but it often has destructive effects (Bradshaw, 2005; Dolezal & Gibson, 2022; Ng, 2020). Thus, real tensions persist between accountability and healing via the digital sphere, as a societal emphasis on punishment rather than growth and transformative justice reveals limitations for digital accountability mechanisms. So, as bell hooks asks, “how do we hold people accountable for wrongdoing and yet at the same time remain in touch with their humanity enough to believe in their capacity to be transformed?” Alternative approaches beyond punitive carceral logic are necessary in order to create and maintain lasting justice models rooted in restoration, transformation, community, and love. Furthermore, because the digital sphere is often a microcosm of the physical world, will it be possible for digital technologies to support these alternative justice models?